Agosto : una reunión familiar dificil de olvidar - Wells, John; Streep, Meryl, 1949-; Roberts, Julia; Speak Up (Barcelona RBA revistas, 2013)
A look at the lives of the strong-willed women of the Weston family, whose paths have diverged until a family crisis brings them back to the Oklahoma house they grew up in, and to the dysfunctional woman who raised them.
País y año de producción : EEUU, 2013
Basada en la obra ganadora del Pulitzer y del premio Tony de Teatro
John Wells; Meryl Streep; Dermot Mulroney; Julia Roberts
No recomendada para menores de 16 años
Acompaña a la revista Speak Up no. 354
Idiomas : Inglés y castellano. Subt.: inglés (subtítulos speak up) y castellano
Keywords: Películas cinematográficas -- DVD